2003
DOI: 10.1165/rcmb.2003-0061oc
|View full text |Cite
|
Sign up to set email alerts
|

The Heparan Sulfate Proteoglycan GPC3 Is a Potential Lung Tumor Suppressor

Abstract: Recently, we used gene expression profiling of lung adenocarcinoma and paired normal tissue from smokers and nonsmokers to identify genes and molecular pathways associated with cigarette smoking and lung carcinogenesis. The gene encoding Glypican 3, a glycosylphosphatidylinositol-linked heparan sulfate proteoglycan, was decreased in lung adenocarcinoma. Within nonmalignant lung, GPC3 expression was decreased in smokers compared with nonsmokers; indicating that expression is associated with cigarette smoking. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 32 publications
5
76
1
Order By: Relevance
“…These data suggest that GPC3 may be a lung tumor suppressor gene involved in cigarette smoke-associated lung carcinogenesis. 19 In our study, Xq26 was the most frequently deleted region; however, a relationship between this LOH and cigarette smoke in atypical carcinoids and large cell neuroendocrine carcinomas seems to be unlikely because the same region was unaffected in small cell lung carcinoma, a lung cancer strongly associated with smoke. 20 Interestingly, in a single case of atypical carcinoid (#13), a relation of LOH restricted to the two markers at Xq26 with tumor histological arrangement was found, with the losses occurring only in the solid but not in the trabecular component of the tumor.…”
Section: Discussioncontrasting
confidence: 50%
“…These data suggest that GPC3 may be a lung tumor suppressor gene involved in cigarette smoke-associated lung carcinogenesis. 19 In our study, Xq26 was the most frequently deleted region; however, a relationship between this LOH and cigarette smoke in atypical carcinoids and large cell neuroendocrine carcinomas seems to be unlikely because the same region was unaffected in small cell lung carcinoma, a lung cancer strongly associated with smoke. 20 Interestingly, in a single case of atypical carcinoid (#13), a relation of LOH restricted to the two markers at Xq26 with tumor histological arrangement was found, with the losses occurring only in the solid but not in the trabecular component of the tumor.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies have demonstrated that GPC3 expression is downregulated in gastric (Ushiku et al, 2009), breast (Xiang et al, 2001), and lung cancers (Kim et al, 2003), but is upregulated in liver cancer and melanoma (Komori et al, 2010). The present study demonstrated that the overall expression rate of GPC3 protein in lung cancer was 45%.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded at a density of 250 000/well and treated with single drugs and concomitant drug stimulation for 12 h. For sequential drug treatment, each treatment at IC 50 was 12 h. Apoptosis was quantified as reported previously (Kim et al, 2003). Briefly, phosphatidylserine translocation was measured using the Annexin V-PI Apoptosis Detection Kit (BD Biosciences, San Diego, CA, USA) for fluorescence labeling and the FACScan for measurement of the resulting fluorescence.…”
Section: Apoptosis Analysismentioning
confidence: 99%